On Old Age: A Relational Account of Agency and Meaning in Later Life - Symons, Xavier (The Hastings Center report, 2026)
Cicero's treatise On Old Age offers an optimistic account of aging and responds to the prejudiced arguments of those who might otherwise ridicule older members of Roman society. While Cicero's rhetoric is, at times, scientifically naive and moralistic, this article argues that there are important insights that can be gained from carefully theorizing later life as a distinct and valuable stage of human existence—a stage of life that ought not be reduced to a mere proxy for health risk. A careful analysis provides insight into the conditions for flourishing in later life notwithstanding a more pronounced expression of the aging process. Some scholars downplay possibilities for agency and meaning in later life and foreground dignity as an overarching value for old age. We argue, however, that agency and meaning are not only possible but also central in later life but must be supported by social relationships that enhance well-being and the pursuit and realization of life goals.